PROBLEMATIKA MANAJEMEN PENGELOLAAN SAMPAH KOTA PEKANBARU TAHUN 2016 - ', Isril; Febrina, Rury (Nakhoda: Jurnal Ilmu Pemerintahan, 2017)
The development dynamics of Pekanbaru City is so rapid and accompanied by rapid populationgrowth has brought consequences on increasing the volume of waste from the community. Therapid growth of population, industry, investment and trade in Pekanbaru City produces domesticwaste of approximately 1,100 tons per day. With the amount of waste generated in such a way, theenvironmental conditions of Pekanbaru City, especially the community settlements, fall into thecategory of complex hygiene issues. The Waste Management consisting of Planning, Organizing,Staffing, Motivating, and Supervision/Controlling.